Quercetin down-regulated bcl-2 gene expression in human leukemia HL-60 cells - Xiao Dong; Gu Zhen-Lun; Zhu Shou-Peng (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of quercetin (Que) on bcl-2 gene expression in human leukemia HL-60 cells. METHODS: Immunohistochemical analysis and RNA Dot blot hybridization were used to identify the expression of bcl-2 genes. RESULTS: The expression of bcl-2 protein was 94% in control HL-60 cells, which became 45%-84% when they were cultured with Que 15-60 mumol.L-1 for 48 h. The expression of bcl-2 mRNA in HL-60 cells was obviously decreased in treatment with Que 15-60 mumol.L-1. CONCLUSION: The apoptotic action of Que in HL-60 cells was associated with the down-regulation of the apoptosis-suppressing gene bcl-2.